Developing Supplementary Sociolinguistic Material in Youtube Channel to Stimulate the Students’ Critical Thinking in Hybrid Class - Caltira Rosiana; Anita Budi Rahayu (Equilibrium: Jurnal Pendidikan, 2022)
The objective of this particular research and development is to produce the supplementary sociolinguistic materials to encourage the students’ critical thinking in hybrid class. Based on the preliminary study conducted by the researcher, it was discovered that most of the learner lacked motivation to understand the core book of sociolinguistic. Then, the lecturer should be creative in hybrid class. Because of this situation, the researcher design the hybrid learning process toward YouTube channel to solve the students’ problems. The researcher use Research and Development with some steps conducting need assessment, material development, validation product, implementation of product, and final product. The product designed with Productive Reading Technique which has the similarity activities with standard KKNI curriculum. The researchers are going to collect the relevant information with guided questionnaire for the students, the lecturer’ interviews, and the checklist form and the suggestion from the expert validations. The data result is described the strongest and the weakness of Sociolinguistic material development. The implication of this product was divided into three points namely, the students could achieve the reading skill with average 81%, the students’ motivation average 91% and around 83% of the student could give the responses base on the critical thinking.